Pengaruh Perendaman Gigi Dengan Teh Hijau (Camellia Sinensis) Terhadap Kekerasan Gigi Setelah Direndam Dengan Minuman Bersoda - Dina Kharina Ramadhani; Hidayati Hidayati; Didin Kustantiningtyastuti (Andalas Dental Journal, 2021)
Tooth erosion is the loss of important dental structure minerals due to continuous acid exposure, due to the low pH and high calories found in soft drinks. Loss of mineral elements in tooth enamel reversible or can still return to normal through the process of remineralization. Adding fluorine, calcium, phosphorus from green tea can increase resistance from remineralization of email toward acids, in other words it can inhibit acid formation by binding to enamel minerals and forming fluorapatite compounds. Objective: To determine the increase of tooth hardness enamel after being soaked with green tea (Camellia Sinensis) toward the teeth soaked with soft drinks using the Vicker Hardness Tester. Research method: This study is a true experimental study with a pre-test and post-test with control group design. The samples of this study were upper premolar teeth adjusted for inclusion criteria. 10 samples were immersed in carbonated drinks for 25 hours, then the samples were divided into two groups, 5 samples were immersed in green tea and the other 5 samples were soaked in artificial saliva for 25 hours. Measurement of tooth hardness using the Vicker Hardness Tester. Results: The data was analysed using paired t-test. Tooth hardness decreased after being soaked with the carbonated drinks (mean = 42.80 with DS = 6.98), then increased after being soaked with green tea (mean = 95.39 with DS = 10.86), p <0.001 also increased in the saliva group (mean = 76.29 with DS = 11.33). Conclusion: There is the effect of immersion with green tea (Camellia sinensis) on the hardness of the enamel surface of the teeth after soaking with soft drinks.